Insights into epigenetic landscape of recombination-free regions - Termolino, Pasquale (Chromosoma, 2016)
Genome architecture is shaped by gene-rich and repeat-rich regions also known as euchromatin and heterochromatin, respectively. Under normal conditions, the repeat-containing regions undergo little or no meiotic crossover (CO) recombination. COs within repeats are risky for the genome integrity. Indeed, they can promote non-allelic homologous recombination (NAHR) resulting in deleterious genomic rearrangements associated with diseases in humans. The assembly of heterochromatin is driven by the combinatorial action of many factors including histones, their modifications, and DNA methylation. In this review, we discuss current knowledge dealing with the epigenetic signatures of the major repeat regions where COs are suppressed. Then we describe mutants for epiregulators of heterochromatin in different organisms to find out how chromatin structure influences the CO rate and distribution.